Decubitus positioning, a free method to allow access, organ protection in thermal ablation and exclusion of liver involvement of an anterior cortex renal tumour - Tan Zehao; Teo Jin Kiat; Terence Lim Say Kiat; Poh Wee Teng; Ng Keng Sin (Archive of Urological Research - Peertechz Publications, 2020)
Renal tumours are getting detected earlier and smaller owing to increase in imaging volume with renal cell carcinoma as one the top 10 most common cancer in Singapore. With ageing population, this is expected to be seen in patients with multiple co-morbidities raising challenges for surgical management. Exclusion of hepatic invasion by renal tumours in the anterior cortex is usually difficult. Access for biopsy and ablation of renal tumours at the anterior cortex is also an issue with trans-hepatic, retroperitoneal approaches risking injury to the liver and posterior aspect of the kidney and an anterior trans-peritoneal approach risking bowel perforation and tract seeding.  The liver is an intra-peritoneal organ while the kidney is retroperitoneal. With this anatomical knowledge, we present a case which uses decubitus positioning to provide path for access, organ protection and to exclude hepatic involvement. This is free and serves as an example for cost saving measure in an economy of rising healthcare cost due to an aging population.